Epidemiology of Klebsiella pneumoniae bloodstream infections in a teaching hospital: factors related to the carbapenem resistance and patient mortality. Issue 1 (December 2016) - Tian, Lijun; Tan, Ruoming; Chen, Yang; Sun, Jingyong; Liu, Jialin; Qu, Hongping; Wang, Xiaoli
Abstract Background AlthoughKlebsiella pneumoniae bloodstream infections (KP-BSIs) have recently attracted attention due to an alarming raise in morbidity and mortality, there have been few reports on the epidemiology of KP-BSIs in mainland China. We sought to describe the epidemiological, microbiological, and clinical characteristics of KP-BSIs, focusing on the risk factors of carbapenem resistance and patient mortality. Methods A retrospective analysis of WHONET data of KP-BSI patients admitted to a teaching hospital in Shanghai, China, between January 1, 2011 and December 31, 2015 was performed, and the annual percentage of patients with carbapenem-resistantK. pneumoniae (CRKP) was determined. Risk factors related to the carbapenem resistance and patient mortality were analyzed using binary logistic regression model. The genetic relatedness of CRKP strains isolated from intensive care unit (ICU) patients was determined by pulsed-field gel electrophoresis (PFGE). Results A total of 293 incidences of KP-BSIs were identified in a 5-year period, 22.18% of these (65/293) were CRKP strains, and the proportion of CRKP-BSI in ICU was 59.62% (31/52), equaling the levels observed in the epidemic regions. A number of KP-BSIs (114), obtained from January 1, 2014, to December 31, 2015, were further investigated. Skin and soft tissue infection source (odds ratio [OR] 26.63, 95% confidence interval [CI] 4.8–146.8) and ICU-acquired infection (OR 5.82, 95% CI 2.0–17.2) was shown to be powerful risk factors leading to the development of CRKP-BSI. The crude 28-day mortality rates of KP-BSI and CRKP-BSI patients were 22.8% and 33.3%, respectively. Lung as the probable source of infection (OR 4.23, 95% CI 1.0–17.3), and high Sequential Organ Failure Assessment (SOFA) score (OR 1.40, 95% CI 1.2–1.6) were strong prognostic factors determining crude 28-day KP-BSI mortality rates. PFGE analysis demonstrated that 10/11 random CRKP isolates in ICU belonged to the same clonal type. Conclusions During the study period, we observed a significant increase in the occurrence of CRKP infections among the identified KP-BSIs in our hospital and especially in ICU, and we demonstrated that carbapenem resistance is associated with the increased mortality of KP-BSI patients.